Development of Embryo Gas Bladder in mosquito fish Gambusia affinis (Baghdad Science Journal, 2011)
2 - 5,5 cm mosquito fishes (Gambusia affinis) were collected from brooks of Baghdad university . This study aimed to identify the histological structure and embryonic development of the gas bladder .The results revealed that the gas bladder of the adult fish consists of single chamber, paraphysoclistous , and its wall consist of three layers. The primordium of the gas bladder appears in 2,5 mm fish embryo as an evagination from the right side of endoderm of foreguts wall. This primordium consists of two thecae, inner, is simple columnar epithelium and outer originates from undifferentiated mesoderm. Simultaneously with the appearance of gas gland in the ventral side of the sac in 4 mm embryo, morphological and histological changes have taken place for it. However the pneumatic duct protrude Change occurs in the site of pneumatic duct in 5mm embryo from the right side into dorsal right side of the forgut wall. In 7mm embryo , the wall of the gas bladder distinguish in to three layers and the endothelium of it consists of changeful epithelium (in 8